Celecoxib Improves Host Defense through Prostaglandin Inhibition during Histoplasma capsulatum Infection - Priscilla Aparecida Tartari Pereira; Bruno Caetano Trindade; Adriana Secatto; Roberto Nicolete; Camila Peres-Buzalaf; Simone Gusmão Ramos; Ruxana Sadikot; Claudia da Silva Bitencourt; Lúcia Helena Faccioli (Mediators of Inflammation)
Prostaglandins act as mediators of inflammation and, similar to cytokines, function as immune modulators during innate and adaptive immune responses. Therefore, using a pharmacological inhibitor, celecoxib, we investigated the role of prostaglandins in host defense against Histoplasma capsulatum infection in C57BL/6 mice. Our results showed that treatment with celecoxib inhibited cyclooxygenase 2, reduced the total fungal burden, and reduced the concentration of PGE2, cytokines, lymphocytes, neutrophils, and mononuclear cells in the bronchoalveolar space and lung parenchyma. In addition, celecoxib treatment increased the synthesis of nitric oxide, IFN-γ, LTB4, and the phagocytic capacity of alveolar macrophages. Moreover, celecoxib treatment increased the survival of mice after infection with a lethal inoculum of H. capsulatum. These results suggest that prostaglandins alter the host immune response and play an important role in the pathogenesis of histoplasmosis. Thus, the inhibition of prostaglandins could be a valuable immunomodulatory strategy and antifungal therapy for histoplasmosis treatment.